2008
DOI: 10.1109/tbme.2007.910681
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Noninvasive Measurement Technique for Analyzing the Pressure Pulse Waveform of the Radial Artery

Abstract: Previous noninvasive measurements of the pulse waveform of the radial artery have not employed standard positioning procedures. Here, we propose a new noninvasive measuring apparatus that has a two-axis mechanism and employs a standard positioning procedure for detecting the optimal site for accurately measuring the pressure pulse waveform (PPW). A modified sensor was designed to simultaneously measure the arterial diameter changed waveform (ADCW) and PPW. Considering the artery as a cylinder, the measured wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 16 publications
1
60
0
Order By: Relevance
“…[1][2][3][4][5][6] Spatial and temporal properties are also needed for analyzing the arterial circulation. 7,8 For this purpose, many noninvasive instruments and analysis methods have been proposed, [9][10][11][12] most of which, however, have focused on the cardiovascular system. On the other hand, recent progress in hemodynamics has attracted lots of attention and has led to more discoveries about the physiology of the arterial circulation system, such as the relations among age, gender, drugs, and the wrist arterial pulse waveforms.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Spatial and temporal properties are also needed for analyzing the arterial circulation. 7,8 For this purpose, many noninvasive instruments and analysis methods have been proposed, [9][10][11][12] most of which, however, have focused on the cardiovascular system. On the other hand, recent progress in hemodynamics has attracted lots of attention and has led to more discoveries about the physiology of the arterial circulation system, such as the relations among age, gender, drugs, and the wrist arterial pulse waveforms.…”
Section: Introductionmentioning
confidence: 99%
“…So there is a need to develop systems with continuous waveform analysis of pulse pressure to avoid such errors. The aim of this study is to develop a noninvasive [3],strap based [5], reliable system along with feature extraction algorithm [7] for diagnostic purposes and to evaluate various pulse parameters such as reflection index, stiffness index to estimate various arterial properties and onset of hemorrhagic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…And the focus of pulse diagnosis machine has shifted over the past few years from an emphasis on evidence of quantifiable pulse diagnosis to attention being paid to standard procedures of quantifiable pulse diagnosis. Tyan et al indicated the standard positioning procedure for detecting the optimal site for accurately measuring the pressure pulse waveform [12]. Yoon et al pointed out that varying contact pressure was needed in pulse-taking procedure [13].…”
Section: Introductionmentioning
confidence: 99%